Experimental investigation on flexural behaviour with cold-formed steel cut-curved channel - Benny, Chan (2015)
This paper investigates on flexural behaviour for cold-formed steel beam. Cold-formed steel is getting popular over the years in construction industry. However, due to its thin-walled behaviour, cold-formed steel is prompt to have buckling failure. Previous research were done to provide stiffener in order to overcome this problem. Furthermore, as addressed in this paper, curved section is introduced and studied to determine its behaviour compare to straight member in handling deformation. Both straight and curved cold-formed steel were tested under flexural with different length as the investigation variable. The results were analysed for comparison. Curved section of cold-formed steel behave differently in beam and column compared to straight section. Curved section has an advantage in reducing the deflection for structural members for flexural behaviour.